Kradja dragulja - Kristl, Vlado (Yogoslavia, 1959)
Satirical cartoon featuring a jewel robbery.
The film is contained with other pieces by Kristl: La peau de chagrin 1960, (10 min.), Don Kihot 1961, (11 min.), General i resni clovek 1962, (10 min.), Madeleine, Madeleine 1963, (10 min.), Der Damm 1964, (77 min.), Prometheus 1966, (10 min.), Italienisches Capriccio 1969, (28 min.), Film oder Macht 1970, (101 min.), Tigerkäfig 1971, (14 min.).
Languages: German, French, English. Options for the subtitles: German, French, English.